2018
DOI: 10.1111/geb.12804
|View full text |Cite|
|
Sign up to set email alerts
|

Cold and dark captivity: Drivers of amphibian longevity

Abstract: Aim Longevity is a critical life‐history trait of organisms. Multiple abiotic and biotic factors are thought to exert different selection pressures, resulting in a great variation in species longevity. We examined factors that, according to evolutionary theories of senescence, are thought to be related to extrinsic and intrinsic mortality rates, and thus shape the variation in longevity among amphibians. Location World‐wide. Time period Present. Major taxa studied Amphibia. Methods We collected literature data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 66 publications
6
31
0
Order By: Relevance
“…Across‐species comparisons indicate that larger endotherms live longer than smaller ones ( r 2 = .46 and .39 in birds and mammals, respectively; Speakman, 2005). In contrast, body size explains only a small portion of the variance in longevity in vertebrate ectotherms, as observed in amphibians ( r 2 = .07–.14; Stark & Meiri, 2018) or reptiles ( r 2 = .04–.23; Stark, Tamar, Itescu, Feldman, & Meiri, 2018). The weaker correlation between body size and maximum lifespan in vertebrate ectotherms than in endotherms probably indicates that the traits have evolved at least partially independently in species with indeterminate growth.…”
Section: Global Warming Fast Growth and Ageing In Ectothermsmentioning
confidence: 97%
“…Across‐species comparisons indicate that larger endotherms live longer than smaller ones ( r 2 = .46 and .39 in birds and mammals, respectively; Speakman, 2005). In contrast, body size explains only a small portion of the variance in longevity in vertebrate ectotherms, as observed in amphibians ( r 2 = .07–.14; Stark & Meiri, 2018) or reptiles ( r 2 = .04–.23; Stark, Tamar, Itescu, Feldman, & Meiri, 2018). The weaker correlation between body size and maximum lifespan in vertebrate ectotherms than in endotherms probably indicates that the traits have evolved at least partially independently in species with indeterminate growth.…”
Section: Global Warming Fast Growth and Ageing In Ectothermsmentioning
confidence: 97%
“…Alternatively, larger-bodied species have lower basal metabolic rate which is correlated with increased longevity in endotherms 50 . In particular, there are evidences that body size is positively correlated with longevity across taxa in both endotherms and ectotherms 2,4,5,27,30,51 . Body size is positively associated with longevity across amphibians and within the large amphibian orders 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have found longevity to be strongly associated with both intrinsic and extrinsic mortality rates in animal kingdoms 2,4,17,2831 . For example, the use of poison and nocturnality, which ascribe to reduced predation pressure (low extrinsic mortality rate) are associated with longer longevity in amphibians 4 . Stark et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of amphibians exposed to seasonal environments can be determined through skeletochronology (the counting of lines of arrested growth in bone cross sections; for a review see, for example, Sinsch 2015), and a large body of literature using this method has revealed that demographic population structures can vastly differ across latitudes and altitudes both within as well as between species (e.g. Zhang and Lu 2012;Oromí et al 2012;Hjernquist et al 2012;Liao et al 2016;Sinsch and Dehling 2017;Stark and Meiri 2018). Because time-limited growth determines size which in turn is related to fecundity, longevity in amphibians can be interpreted as the result of life history strategies to maximise reproductive output under given constraints (Sinsch et al 2010).…”
Section: Introductionmentioning
confidence: 99%